2023
DOI: 10.1002/adfm.202214450
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscaling and Heterojunction for Photocatalytic Hydrogen Evolution by Bimetallic Metal‐Organic Frameworks

Abstract: Using sunlight to manufacture hydrogen offers promising access to renewable clean energy. For this, low‐cost photocatalyst with effective light absorption and charge transfer are crucial, as current top‐performing systems often involve precious metals like Pd and Pt. An integrated organic–inorganic photocatalyst based on the cheap metals of iron and nickel are reported, wherein the metal ions form strong metal‐sulfur bonds with the organic linker molecules (2,5‐dimercapto‐1,4‐benzenedicarboxylic acid, H4DMBD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…[44] In addition, the Ni-O 2 S 2 was constructed by choosing the benzene ring of terephthalic acid (TPA) modified with sulfhydryl as ligand molecules (Figure 5i). [45] The preparation strategy of SACs based on ligand engineering provides a feasible idea for us to obtain SACs with various exact configurations and has a great prospect of accurately controlling the reactivity and selectivity.…”
Section: Ligand Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] In addition, the Ni-O 2 S 2 was constructed by choosing the benzene ring of terephthalic acid (TPA) modified with sulfhydryl as ligand molecules (Figure 5i). [45] The preparation strategy of SACs based on ligand engineering provides a feasible idea for us to obtain SACs with various exact configurations and has a great prospect of accurately controlling the reactivity and selectivity.…”
Section: Ligand Engineeringmentioning
confidence: 99%
“…i) Synthetic scheme of M 2 DMBD-NS (nanosheet) and M 2 DMBD-PL (thick platelet) (M = Fe or Ni). Reproduced with permission [45]. Copyright 2023, Wiley.…”
mentioning
confidence: 99%
“…3(B), (C) and 4(A), (B)). Among them, the studied active metals are Fe–Ni, 88–90 Fe–Zr, 91 Fe–Mn, Fe–Co, 92 Cu–Zn, 92,93 Mn–Zn, 94 and Co–Mn–Zn. 95 The electron density difference map of [Fe 2 Ni 4 ], as calculated and simulated, shows that the electron density at the Fe center decreases, while that at the Ni center increases.…”
Section: Mofs@dzs Classification By Metal Ionsmentioning
confidence: 99%
“…88 Besides, the electrons were transferred from the Fe center to the Ni center. 89 Bader charge analysis showed that each Ni center accepted, on average, 0.76 electrons from the Fe center. In addition, the d orbital partially occupied by transition metals Fe and Co could receive electrons from the N 2 σ-orbital and provide electrons to the empty π*-orbital of N 2 , and the co-introduction of Fe and Co enhanced the Fe and Co bimetallic interaction, reducing the reaction activation energy and improving the catalytic activity, thereby enhancing Dz adsorption.…”
Section: Mofs@dzs Classification By Metal Ionsmentioning
confidence: 99%
“…Since its debut in 2009, , the linker molecule H 2 DMBD (2,5-dimercaptobenzenedicarboxylic acid) has opened two directions for coordination network [also known as the metal–organic framework (MOF)] materials. On one hand, transition metal ions (e.g., M = Cu + , Fe 2+ , Co 2+ , and Ni 2+ ) and other soft metal ions (Pb 2+ ) engage the thiol groups (−SH) to form solid frameworks with enhanced conductive and electroactive properties. Highlights here include the 2D system M 2 DMBD reported in 2022, which was also shown to be amenable with ion intercalations between the metal–thiolate layers, so as to conveniently modify the electronic and redox properties . On the other hand, very hard metal ions (e.g., Eu 3+ , Al 3+ , and Zr 4+ ) selectively engage the carboxyl units to form open frameworks (e.g., the now commercialized ZrDMBD solid), with free-standing mercapto groups for functionalization.…”
Section: Introductionmentioning
confidence: 99%